El Código Penal argentino de 1922 comentado por el diario La Nación (1917-1924) - Levaggi, Abelardo (2019)
In 1921, the Argentine Republic enacted its second national Criminal Code, which came into force the following year. The work exposes and glosses the comments that the newspaper La Nación of Buenos Aires, one of the most important in the country, dedicated to the process of editing and enactment of the Code. Without being a specialist journal in legal subjects, but of common information, La Nación dealt in several notes of this subject, not in a systematic way but with interesting comments to the public opinion on some shares of the problem.